(untitled) (Journal of the College of Languages (JCL), 2014)
Honorifics are linguistic expressions which maintain social as well as religious respect to other people. They are linguistic techniques which express politeness to other interlocutors. Semantically speaking, honorifics are of two types: al-Laqab (title) and al-Kuniya (teknonyms) following a specific word order. They form part of the Arab recognitions and are mold into their social and communicative competence. The study focuses upon religious and regional honorifics which convey deference and respect. It assumes that religious and cultural recognitions play vital roles in formulating and embedding the sense of honorifics. It is hypothesized that Arab people express respect to religious personalities by using honorific titles. Also, religious honorifics involve collocations of a special kind which co-occur only with religious persons and places.